A revision of the theory of fundamental legal concepts - Orunesu, Claudina (Revus (Ljubljana), 2019)
Although they come from different traditions, Hans Kelsen and W. N. Hohfeld have offered two essential contributions to the clarification of fundamental legal concepts. After a brief review of their proposals, certain problematic aspects of their reconstructions will be analyzed in the light of categories developed by Eugenio Bulygin, in particular his criticism of the reductionist conceptions of norms, the non-prescriptive character of power-conferring rules, and the distinction between norms and norm-propositions. On this basis, and starting from the concept of legal obligation, an outline of an alternative reconstruction of the theory of fundamental legal concepts will be presented.
Keywords: fundamental legal concepts; law; legal obligation; normativnost; norme; norm-propositions; norms; power conferring norms; pravo; sanction